Artists at School–developing Pupils' Social Interaction through Artist-teacher Co-operation. (16th January 2015) - Ruokonen, Inkeri; Ruismäki, Heikki
Abstract: The research is a case study of teacher-artist co-operation in one primary school in a metropolitan area in Finland. In this case study, the artists worked at school with teachers and learning at the school was planned through arts-based, co-operative teamwork. The aim of this study is to evaluate how social skills were developed during the project. The research task was to determine whether the long-term artist pedagogy and co-operation at school have any significant connection to the social skills and behaviour of the pupils. Data has been collected through teacher-based evaluations of pupils' social skills during the school days and by interviewing the artists and teachers. Primary school teachers were asked to describe the behaviour and verbalisation of the pupils. Altogether 32 pupils from 3rd grade participated in this case study. Half of the pupils participated in an artist's class and half formed the control group. The teachers' descriptions of the pupils' behaviour were analysed. The artist group also used some music and drama. Two artists worked with the test group weekly during a period of six months. The measures used were Likert-based evaluation scores of pupils' social behaviour in everyday situations at school. According to the results, the artist-teacher co-operation and learning through the arts are worthwhile tools to develop pupil's social skills and learning in Finnish schools.